Multicolour versus monocolour inking specimens after pancreaticoduodenectomy for periampullary cancer: A single centre prospective randomised clinical trial. (March 2018) - Casadei, Riccardo; Ricci, Claudio; Taffurelli, Giovanni; Pacilio, Carlo Alberto; Santini, Donatella; Di Marco, Mariacristina; Minni, Francesco
Abstract: Background: R status represents an important prognostic factors in periampullary cancers. Thus, it is useful to verify if it can be influenced by different techniques of margination. Methods: Single-centre, randomised clinical trial of patients affected by periampullary cancer who underwent pancreaticoduodenectomies which included two different types of margination: arm A (multicolour inking) and arm B (monocolour inking). The primary endpoint was the overall R1 resection rate and its difference between the two arms. The secondary endpoints were the R1 resection rate in each margin and its difference between the two arms, and the impact of margin status on survival. Results: Fifty patients were randomised, 41 analysed: 22 in arm A, 19 arm B. The overall R1 status was 61%, without significant differences between the two arms. The margin most commonly involved was the superior mesenteric artery (SMA) (36.6%). A trend in favour of arm B was shown for the superior mesenteric artery margin (arm A = 22.7% versus arm B = 52.6%; P = 0.060). The anterior surface (P = 0.015), SMA (P = 0.047) and pancreatic remnant (P = 0.018) margins significantly influenced disease-free survival. Conclusions: The R status was not influenced by different techniques of margination using a standardised pathological protocol. The SMA margin seemed to be the most important margin for evaluating both R status and disease-free survival. Highlights: To test two different pathological techniques of margination after pancreaticoduodenectomy for periampullary cancer. A randomised clinical trial was performed and fifty patients were randomised, 41 analysed. The overall R1 status was 61% without significant differences between the two groups. The SMA margin seemed to be the most important margin for evaluating both R status and disease-free survival.